Prevalence of gingival recession and associated etiological factors among the school children - Sonia Sudeepthi Seemakurthy; Sailavanya Nuvvula; Sreekanth Kumar Mallineni; Sivakumar Nuvvula (Wolters Kluwer Medknow Publications, 2022)
Objective: The objective of this study is to assess the prevalence of gingival recession (GR) and associated etiological factors among school children. Methodology: The study sample consisted of 2095 children from the Nellore region divided into three groups of age ranges from primary dentition (<7 years), mixed dentition (7-12 years), and permanent dentition (>12 years) respectively, attending the department of pediatric and preventive dentistry and the school dental health programs organized by the department. The clinical examination involved measuring GR using William's periodontal probe and evaluating associated etiological factors. Data were statistically analyzed using the Chi-square test. Results: The GR among the study population was 7.9% (n = 165). Among them, males were 46% and females were 54% (P > 0.05). The GR was more in children in the 7-12 years age group (75%), followed by <7 years (21%) and >12 years (4%) age groups. The associated factors include malocclusion (69%), deleterious habits (5%), and anomalies (26%). Anomalies showed an association with GR (P < 0.05) compared to malocclusion and deleteriousness habits (P > 0.05). Conclusion: The prevalence of GR is 7.9%, and GR is more prevalent in males and the 7-12 years age group. GR is associated with transient malocclusion, deleterious habits, and anomalies.